Complex and method for producing complex
The composite material, comprising a polyamide compound with specific dicarboxylic acid and diamine units and glass fibers, addresses the limitations of conventional biopolymers by enhancing mechanical strength and reducing water absorption, thereby expanding its application scope.
Patent Information
- Application Number
- JP2023175469
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
AI Technical Summary
Conventional biopolymers lack sufficient mechanical strength and other properties for certain applications, necessitating the development of materials with improved properties.
A composite material comprising a polyamide compound with specific dicarboxylic acid and diamine units, combined with glass fibers, to enhance mechanical strength and other properties.
The composite material exhibits significantly improved tensile and bending properties, as well as a lower water absorption rate, compared to conventional biopolymers, making it suitable for a wide range of applications.
Smart Images

Figure 2025065929000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to composites and methods for making the composites. [Background technology]
[0002] In recent years, from the viewpoints of preventing global warming and reducing the risks of resource depletion, polyamide compounds (hereinafter also referred to as biopolymers) made from plant-derived compounds as starting materials have been attracting attention as alternative polymers to petroleum-based polymers (Patent Document 1, Non-Patent Documents 1 and 2, etc.).
[0003] However, conventional biopolymers do not necessarily have sufficient properties depending on the application, and there is a demand for improving the properties. Therefore, attempts have been made to improve the properties. For example, Patent Document 2 discloses a composite containing a polyamide compound based on the polyamide compound described in Patent Document 1 and talc. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-137788 A [Patent Document 2] Patent Publication No. 2022-162256 [Non-patent literature]
[0005] [Non-Patent Document 1] C. -H. Lee, H. Takagi, H. Okamoto, M. Kato, A. Usuki. J. Polym. Sci. Part A: Polym. Chem. 47, 6025 (2009). [Non-Patent Document 2] C. -H. Lee, H. Takagi, H. Okamoto, M. Kato. J. Appl. Polym. Sci. 127, 530 (2013). Summary of the Invention [Problem to be solved by the invention]
[0006] The composite disclosed in Patent Document 2 has succeeded in improving the properties such as tensile strength, flexural modulus, and tensile modulus of the polyamide compound disclosed in Patent Document 1. Therefore, it can be said that the composite contributes to improving the properties of conventional biopolymers.
[0007] However, in order to expand the applications of biopolymers, it is desirable to have a material that has even better properties, such as mechanical strength, than the composite disclosed in Patent Document 2.
[0008] Therefore, one aspect of the present disclosure aims to provide a material that has significantly improved properties compared to conventional biopolymers. [Means for solving the problem]
[0009] In order to solve the above problems, a composite according to one embodiment of the present disclosure includes a polyamide compound containing dicarboxylic acid units represented by the following general formula (1), dicarboxylic acid units represented by the following general formula (2), and diamine units represented by the following general formula (3), and a glass fiber.
[0010] [ka]
[0011] (wherein x is an integer from 6 to 12, y is an integer from 8 to 18, and n is an integer of 1 or more.)
[0012] [ka]
[0013] (z is an integer from 2 to 18.)
[0014] [ka]
[0015] [ka] Effect of the Invention
[0016] According to one aspect of the present disclosure, it is possible to provide a novel material having properties such as mechanical strength that are significantly improved compared to conventional biopolymers. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 shows the tensile modulus of a composite according to the present disclosure compared to the tensile modulus of a conventional biopolymer. [Diagram 2] FIG. 1 shows the flexural modulus of a composite according to the present disclosure compared to the flexural modulus of a conventional biopolymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiments of the present disclosure will be described in detail. In this specification, when a numerical range is described using "to", the range includes the lower limit and the upper limit unless otherwise specified. For example, "6 to 12" means "6 or more and 12 or less". In this specification, "weight" and "mass", "wt%" and "mass%", "parts by weight" and "parts by mass" are treated as synonyms.
[0019] [1] Complex The composite according to the present disclosure includes a polyamide compound containing a dicarboxylic acid unit represented by the following general formula (1), a dicarboxylic acid unit represented by the following general formula (2), and a diamine unit represented by the following general formula (3), glass fiber, It is a complex containing
[0020] [ka]
[0021] (wherein x is an integer from 6 to 12, y is an integer from 8 to 18, and n is an integer of 1 or more.)
[0022] [ka]
[0023] (z is an integer from 2 to 18.)
[0024] [ka]
[0025] [ka]
[0026] (1) Polyamide compounds In the polyamide compound of the present disclosure, the content of the dicarboxylic acid unit is not particularly limited and is usually 5 to 50 mol %, preferably 20 to 50 mol %, and more preferably 30 to 50 mol %.
[0027] In the polyamide compound of the present disclosure, the content of the diamine unit is not particularly limited and is usually 5 to 50 mol %, preferably 20 to 50 mol %, and more preferably 30 to 50 mol %.
[0028] From the viewpoint of the polymerization reaction, the content ratio of the dicarboxylic acid unit and the diamine unit is preferably approximately the same, and the content of the dicarboxylic acid unit is more preferably within ±1 mol % of the content of the diamine unit.
[0029] The polyamide compound of the present disclosure may further contain structural units other than those described above, so long as the effects of the composite of the present disclosure are not impaired.
[0030] (1-1) Dicarboxylic acid unit As described above, the polyamide compound of the present disclosure contains a dicarboxylic acid unit represented by general formula (1) and a dicarboxylic acid unit represented by general formula (2).
[0031] In general formula (1), x is preferably an integer of 8 to 10, and y is preferably an integer of 8 to 14. In addition, in general formula (2), z is preferably an integer of 2 to 6. By having x, y, and z within these ranges, the tensile properties, bending properties, and impact properties of the composite can be improved.
[0032] The dicarboxylic acid unit represented by the general formula (1) is derived from plants, and therefore the composite can contribute to preventing global warming and reducing the risks associated with resource depletion, and can be preferably used as a substitute for petroleum-based polymers.
[0033] When the total amount of dicarboxylic acid units in the polyamide compound of the present disclosure is taken as 100 mol%, the total amount of the dicarboxylic acid units represented by the above general formula (1) and the dicarboxylic acid units represented by the general formula (2) is not particularly limited. The total amount is preferably 30 to 100 mol%, more preferably 50 to 100 mol%, and particularly preferably 70 to 100 mol%. By setting the total amount within this range, a composite having a high flexural modulus and a high glass transition temperature (Tg) can be obtained.
[0034] In the polyamide compound of the present disclosure, the molar ratio of the dicarboxylic acid unit represented by general formula (1) to the dicarboxylic acid unit represented by general formula (2) is not particularly limited.
[0035] The molar ratio of the dicarboxylic acid units represented by general formula (1):the dicarboxylic acid units represented by general formula (2) is preferably 95:5 to 5:95, more preferably 90:10 to 10:90, and further preferably 80:20 to 20:80.
[0036] When the molar ratio is within this range, a certain amount of plant-derived dicarboxylic acid units is contained in the complex, which is preferable from the viewpoint of preventing global warming, etc., as described above.
[0037] Compounds capable of constituting the dicarboxylic acid unit represented by the general formula (1) and the dicarboxylic acid unit represented by the general formula (2) are not particularly limited.
[0038] For example, specific examples of dicarboxylic acid compounds include straight-chain aliphatic dicarboxylic acids having 2 to 25 carbon atoms, such as oxalic acid, malonic acid, fumaric acid, and maleic acid; or aliphatic dicarboxylic acids such as dimerized aliphatic dicarboxylic acids having 14 to 48 carbon atoms (dimer acids) obtained by dimerizing unsaturated fatty acids obtained by fractional distillation of triglycerides and their hydrogenated products (hydrogenated dimer acids); alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 1,3-benzenediacetic acid, and 1,4-benzenediacetic acid. Derivatives of these dicarboxylic acid compounds may also be used. Examples of the derivatives include carboxylic acid halides. These may be used alone or in combination of two or more.
[0039] When the total amount of dicarboxylic acid units in the polyamide compound of the present disclosure is 100 mol%, the content of dicarboxylic acid units other than the dicarboxylic acid represented by the above general formula (1) and the dicarboxylic acid represented by the general formula (2) is not particularly limited. The content of the dicarboxylic acid units is preferably less than 50 mol%, more preferably less than 20 mol%, and particularly preferably less than 10 mol%. When the content of the dicarboxylic acid units is within this range, the tensile strength, tensile modulus, flexural modulus, etc. are improved.
[0040] (1-2) Diamine unit The polyamide compound of the present disclosure contains a diamine unit represented by the general formula (3). When the total amount of diamine units in the polyamide compound of the present disclosure is 100 mol%, the content of the diamine unit represented by the general formula (3) is not particularly limited. The content is preferably 5 to 100 mol%, more preferably 50 to 100 mol%, and particularly preferably 80 to 100 mol%. When the content is within this range, the tensile strength, tensile modulus, bending elasticity, etc. are excellent.
[0041] Repeating units which may be contained in the polyamide compounds of the present disclosure include the following combinations of dicarboxylic acid units and diamine units:
[0042] [A] A combination of a dicarboxylic acid unit represented by general formula (1) and a diamine unit represented by general formula (3).
[0043] [B] A combination of a dicarboxylic acid unit represented by general formula (2) and a diamine unit represented by general formula (3).
[0044] Different kinds of repeating units may be present randomly in the polyamide compound, or the same kind of repeating units may be present in the polyamide compound in the form of blocks.
[0045] The compound capable of constituting the diamine unit other than the diamine unit represented by the general formula (3) is not particularly limited, and examples of the compound include known aliphatic diamines, alicyclic diamines, aromatic diamines, and diaminoorganosiloxanes.
[0046] Examples of the aliphatic diamine include 1,1-meta-xylylenediamine, 1,3-propanediamine, and pentamethylenediamine.
[0047] Examples of the alicyclic diamine include 4,4'-methylenebis(cyclohexylamine) and 1,3-bis(aminomethyl)cyclohexane.
[0048] Examples of the aromatic diamine include o-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 1,5-diaminonaphthalene, 2,2'-dimethyl-4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 2,7-diaminofluorene, 4,4'-diamino-2,2'-dimethylbiphenyl, 9,9-bis(4-aminophenyl)fluorene, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(4-aminophenyl) (p-phenylenediisopropylidene)bisaniline, 4,4'-(m-phenylenediisopropylidene)bisaniline, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 2,6-diaminopyridine, 3,4-diaminopyridine, 2,4-diaminopyrimidine, 3,6-diaminoacridine, 3,6-diaminocarbazole, N-methyl-3,6-diaminocarbazole, N-ethyl-3,6-diaminocarbazole, N-phenyl-3,6-diaminoca Rubazol, N,N'-bis(4-aminophenyl)-benzidine, N,N'-bis(4-aminophenyl)-N,N'-dimethylbenzidine, 1,4-bis(4-aminophenyl)-piperazine, 3,5-diaminobenzoic acid, dodecanoxy-2,4-diaminobenzene, tetradecanoxy-2,4-diaminobenzene, pentadecanoxy-2,4-diaminobenzene, hexadecanoxy-2,4-diaminobenzene, octadecanoxy-2,4-diaminobenzene, dodecanoxy-2,5-diaminobenzene, tetradecanoxy-2,5-diamino Benzene, pentadecanoxy-2,5-diaminobenzene, hexadecanoxy-2,5-diaminobenzene, octadecanoxy-2,5-diaminobenzene, cholestanyloxy-3,5-diaminobenzene, cholestanyloxy-3,5-diaminobenzene, cholestanyloxy-2,4-diaminobenzene, cholestanyloxy-2,4-diaminobenzene, cholestanyl 3,5-diaminobenzoate, cholestanyl 3,5-diaminobenzoate, lanostannyl 3,5-diaminobenzoate, 3,6-bis(4-aminobenzoyloxy)cholestane, 3,6-bis(4-aminophenoxy)cholestane, 4-(4'-trifluoromethoxybenzoyloxy)cyclohexyl-3,5-diaminobenzoate, 4-(4'-trifluoromethylbenzoyloxy)cyclohexyl-3,5-diaminobenzoate, 1,1-bis(4-((aminophenyl)methyl)phenyl)-4-butylcyclohexane, 1,1-bis(4-((aminophenyl)methyl)phenyl)-4-heptylcyclohexane, 1,1-bis(4-((aminophenoxy)methyl)phenyl)-4-heptylcyclohexane Examples of the aryl group include cyclohexane, 1,1-bis(4-((aminophenyl)methyl)phenyl)-4-(4-heptylcyclohexyl)cyclohexane, 2,4-diamino-N,N-diallylaniline, 4-aminobenzylamine, 3-aminobenzylamine, 1-(2,4-diaminophenyl)piperazine-4-carboxylic acid, 4-(morpholin-4-yl)benzene-1,3-diamine, 1,3-bis(N-(4-aminophenyl)piperidinyl)propane, and α-amino-ω-aminophenylalkylene.
[0049] These may be used alone or in combination of two or more.
[0050] When the total amount of diamine units in the polyamide compound of the present disclosure is 100 mol%, the content of diamine units other than the diamine represented by the above general formula (3) is not particularly limited. The content of diamine units other than the diamine represented by the general formula (3) is preferably less than 50 mol%, more preferably less than 30 mol%, and particularly preferably less than 10 mol%. When the content of diamine units other than the diamine represented by the general formula (3) is within this range, the tensile strength, tensile modulus, bending elasticity, etc. are improved.
[0051] (1-3) Degree of polymerization of polyamide compound The degree of polymerization of the polyamide compound of the present disclosure is not particularly limited. The polyamide compound of the present disclosure preferably has a viscosity number, measured as follows, in the range of 4.0 to 10.0, particularly preferably 5.0 to 8.0.
[0052] The viscosity number is measured as follows.
[0053] Test method: Compliant with JIS K6933 Test conditions: Measurement solvent: 96% sulfuric acid Viscometer: Ubbelohde viscometer Solution concentration: 0.005g / mL Measurement temperature: 25℃ Calculation formula: Viscosity number (mL / g)=(t / t0-1)×1 / C t0: Flow time of the measurement solvent (s) t: Flow time of sample solution (s) C: Solution concentration (g / mL) (1-4) Method for producing polyamide compound The method for producing the polyamide compound of the present disclosure is not particularly limited. The polyamide compound of the present disclosure can be produced, for example, by reacting a dicarboxylic acid compound with a diamine compound.
[0054] As the dicarboxylic acid compound, in addition to dicarboxylic acids, carboxylic acid derivatives in which the hydroxyl group of the carboxyl group of the dicarboxylic acid is replaced with another heteroatom (an atom other than carbon, hydrogen, or metal) can also be used. Examples of the carboxylic acid derivatives include acyl halides (acid halides) in which the hydroxyl group is replaced with a halogen.
[0055] The polyamide compound of the present disclosure can be produced by polycondensing a diamine component capable of forming a diamine unit and a dicarboxylic acid component capable of forming a dicarboxylic acid unit. The degree of polymerization can be controlled by adjusting the polycondensation conditions, etc.
[0056] Suitable methods for producing a polyamide compound include, for example, (A) a method using an acid or base catalyst, (B) a method for activating a carboxylic acid, (C) a method using transesterification, and (D) a method using a condensing agent.
[0057] As a suitable production method, for example, a production method is adopted in which a dicarboxylic acid is activated to produce an acid chloride, and the acid chloride is reacted with a diamine to produce a polyamide compound. That is, a production method is preferably adopted in which an acid chloride capable of forming a dicarboxylic acid unit represented by the above general formula (1), an acid chloride capable of forming a dicarboxylic acid unit represented by the above general formula (2), and a diamine capable of forming a diamine unit represented by the above general formula (3) are reacted.
[0058] In addition, if a dicarboxylic acid is activated to form an acid chloride and then reacted with a diamine, a polyamide compound can be produced efficiently.
[0059] During polycondensation, a monoamine and / or a monocarboxylic acid may be added as a molecular weight regulator. In addition, in order to prevent the polycondensation reaction and achieve a desired degree of polymerization, the ratio (molar ratio) of the diamine component and the carboxylic acid component constituting the polyamide compound may be adjusted to be different from 1:1.
[0060] When polymerization is performed by a dehalogenation water reaction by the reaction of a carboxylic acid dihalide such as the above-mentioned acid chloride with a diamine, the reaction proceeds rapidly, so it is preferable to carry out the reaction at a relatively low temperature in order to control the reaction rate. The reaction temperature is preferably in the range of, for example, -10°C to 100°C.
[0061] The reaction solvent is not particularly limited, and a wide variety of known solvents can be used. For example, examples of organic polar solvents as reaction solvents include dimethylacetamide, N-methylpyrrolidone, dimethylsulfone, dimethylformamide, N-methylcaprolactam, tetramethylurea, and N,N'-dimethyl-2-imidazolidinone. These may be used alone or as a mixed solvent of two or more. If necessary, hydrogen chloride, a metal halide salt, such as lithium chloride, calcium chloride, or potassium chloride, may be used in combination to improve solubility.
[0062] The concentration of the polyamide compound (polymer concentration) is not particularly limited, although it depends on the solubility of the produced polyamide compound in a solvent and the solution viscosity. The concentration of the polyamide compound is preferably 0.1 to 40 mass % from the viewpoint of productivity, for example.
[0063] The concentration of the polyamide compound is determined by comprehensively considering the composition and composition ratio of the polyamide compound, its solubility in the solvent, the viscosity of the solution, the handleability of the solution, and the ease of degassing the solution.
[0064] The method of adding the raw materials is not particularly limited. For example, a diamine is added to a reaction solvent, and after dissolving at a low temperature, a dicarboxylic acid halide such as an acid chloride, which is one of the raw materials, is added. In this case, it is preferable to carry out the operation under an inert atmosphere (for example, under a nitrogen atmosphere or an argon gas atmosphere) in order to prevent deterioration of the diamine. The molar ratio of the diamine and the acid halide should basically be equimolar, but in order to control the degree of polymerization, the diamine or the acid component, which is one of the raw materials, may be added in excess. Also, a suitable amount of a monofunctional organic compound, such as aniline, naphthylamine, acetic acid chloride, or benzoyl chloride, may be added.
[0065] In the case of the polyamide compound of the present disclosure, in order to improve the properties, an addition method intended to block the polymer may be adopted, such as reacting a part of the diamine or acid chloride and then adding the remaining raw materials.
[0066] The polymerization reaction product (polyamide compound) thus obtained contains hydrogen halide as a by-product, and therefore requires neutralization. The neutralizing agent is not particularly limited as long as it is a commonly known basic compound.
[0067] As the neutralizing agent, triethylamine, tripropylamine, benzyldimethylamine, lithium hydroxide, sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, magnesium oxide, calcium oxide, tetraethylammonium salt, etc. Although such a neutralizing agent may be added alone in the form of a powder, it is preferable to use the agent finely powdered and dispersed in an organic solvent as a slurry in terms of reactivity and operability.
[0068] The polyamide compound solution obtained by the above method can be separated in a poor solvent such as water, methanol, etc. The solution after the neutralization reaction can also be used as it is as a molding solution.
[0069] In addition, the industrial polycondensation method of the polyamide compound of the present disclosure is not particularly limited, and known methods are widely used. For example, the pressurized salt method, the normal pressure dropping method, the pressurized dropping method, the reactive extrusion method, etc. can be mentioned. In addition, the reaction temperature is as low as possible, so that the polyamide compound can be prevented from yellowing and gelling, and therefore a polyamide compound with stable properties can be obtained.
[0070] The pressurized salt method is a method of melt polycondensation under pressure using nylon salt as a raw material. Specifically, after preparing an aqueous nylon salt solution containing a diamine component, a dicarboxylic acid component, and optionally other components, the aqueous solution is concentrated and then heated under pressure to polycondense while removing condensation water. While gradually returning the pressure inside the vessel to normal pressure, the temperature is raised to about the melting point of the polyamide compound + 10°C and maintained, and then the pressure is gradually reduced to 0.02 MPaG while maintaining the temperature to continue polycondensation. When a certain stirring torque is reached, the inside of the vessel is pressurized to about 0.3 MPaG with nitrogen to recover the polyamide compound.
[0071] In the normal pressure dropping method, a diamine component is continuously dropped into a mixture of a dicarboxylic acid component and, if necessary, other components, which are heated and melted under normal pressure, and polycondensation is carried out while removing the condensed water. Note that the polycondensation reaction is carried out while increasing the temperature of the reaction system so that the reaction temperature does not fall below the melting point of the polyamide compound to be produced.
[0072] In the pressure dropping method, first, a dicarboxylic acid component and, if necessary, other components are charged into a polycondensation tank, and each component is stirred and melted and mixed to prepare a mixture. Next, the diamine component is continuously dropped into the mixture while pressurizing the inside of the tank to about 0.3 to 0.4 MPaG, and polycondensation is performed while removing condensation water. At this time, the polycondensation reaction is performed while raising the temperature of the reaction system so that the reaction temperature does not fall below the melting point of the polyamide compound to be produced. When the set molar ratio is reached, the dropping of the diamine component is terminated, and while gradually returning the inside of the tank to normal pressure, the temperature is raised to about the melting point + 10 ° C of the polyamide compound and maintained, and then the temperature is gradually reduced to 0.02 MPaG while maintaining the temperature, and polycondensation is continued. When a certain stirring torque is reached, the inside of the tank is pressurized to about 0.3 MPaG with nitrogen to recover the polyamide compound.
[0073] The reactive extrusion method is a method for incorporating the compound into the polyamide backbone by a transamidation reaction.
[0074] (2) Glass fiber The glass fiber is not particularly limited as long as it is fibrous glass. The types of glass fiber include, for example, E glass, C glass, S glass, and D glass, and any type of glass fiber may be used. In addition, one type of glass fiber may be used, or two or more types may be used.
[0075] The glass fibers can be prepared by drawing a viscous glass melt to form fibers having a diameter of, for example, 5 to 15 μm, but commercially available products may also be used.
[0076] The glass fiber content in the composite according to the present disclosure is not particularly limited. From the viewpoint of improving the tensile strength, tensile modulus, flexural modulus, etc. of the composite, the content is preferably 5% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 50% by mass or less, and even more preferably 20% by mass or more and 50% by mass or less, with the mass of the entire composite being 100% by mass.
[0077] The glass fiber is preferably surface-treated. This is because the adhesion between the glass fiber and the polyamide compound is improved by the surface treatment. The surface treatment is performed by adsorbing a silane-based treatment agent, such as vinyl silane or acrylic silane, to the glass fiber surface through a dehydration reaction between the Si-OH group of the silane-based treatment agent and the Si-OH group on the glass fiber surface. In the present disclosure, a glass fiber that has been surface-treated in advance may be used.
[0078] (3) Properties of the Complex The composite according to the present disclosure is a composite containing the polyamide compound and the glass fiber. As described in Patent Document 2, a composite of a polyamide compound containing a biopolymer and talc has already been developed. Patent Document 2 shows that the composite has increased tensile strength by about 1.2 times, increased tensile modulus by about 2 times, and increased flexural modulus by about 1.5 times compared to the polyamide compound alone. The composite described in Patent Document 2 can be used as an interior material and an exterior material for automobiles, railway vehicles, ships, airplanes, etc., but if a composite with further enhanced strength can be provided, its applications can be further expanded.
[0079] Therefore, the present inventors conducted extensive research into a material capable of forming a composite with a polyamide compound containing a biopolymer, and capable of increasing the strength of the composite to a level higher than that of the composite described in Patent Document 2. As a result, the inventors found that by using glass fiber instead of talc to form a composite between the glass fiber and the polyamide compound, it is possible to obtain tensile properties and bending properties that are significantly higher than those of the composite described in Patent Document 2.
[0080] As shown in the examples described below, the composite according to the present disclosure has succeeded in increasing the tensile strength by about 2 times, the tensile modulus by about 6 times, and the flexural modulus by about 4.5 times, compared to the case where only the polyamide compound containing the biopolymer is used. In other words, the tensile modulus and flexural modulus of the composite are about 3 times stronger than those of the composite described in Patent Document 2, and the tensile strength is about 1.7 times stronger. In addition, the composite showed results in a Charpy impact test comparable to those of the composite described in Patent Document 2.
[0081] Therefore, the composite according to the present disclosure can impart to a member to which the composite is applied (e.g., an exterior material of an automobile) tensile properties and bending properties that are significantly stronger than those of the composite described in Patent Document 2, and can also impart impact properties equivalent to those of the composite. Moreover, since the composite according to the present disclosure contains a biopolymer, it is a material that imposes a small burden on the environment.
[0082] Based on these properties, the composite according to the present disclosure can be used in a wide range of applications, including those for which conventional polyamide compounds have been used, such as for all components of automobiles, railroad cars, ships, airplanes, etc. Examples of such components include interior and exterior materials.
[0083] Examples of automotive parts include automotive interior materials, automotive instrument panels, and automotive exterior materials. Specific examples include door substrates, package trays, pillar garnishes, switch bases, quarter panels, side panels, armrests, automotive door trims, seat structural materials, seat backboards, ceiling materials, console boxes, automotive dashboards, various instrument panels, deck trims, bumpers, spoilers, cowlings, and the like. Further examples include interior and exterior materials for buildings, furniture, and the like. That is, examples include door surface materials, door structural materials, and surface materials for various furniture (desks, chairs, shelves, chests, and the like). Other examples include packaging bodies, containers (trays, and the like), protective members, and partition members.
[0084] The composite according to the present disclosure has tensile properties and bending properties far superior to those of the composite described in Patent Document 2, and is therefore particularly suitable for use in applications requiring high strength. Examples of such applications include, but are not limited to, exterior materials for automobiles and various instrument panels.
[0085] The present inventors have also found that the composite according to the present disclosure has a significantly low water absorption rate. In general, it is known that conventional polyamides having an aliphatic skeleton (such as nylon 6, nylon 12, and nylon 66) have a high water absorption rate, and that the water absorption rate of biopolymers is lower than that of the polyamides. The present inventors have now found that the composite according to the present disclosure exhibits a lower water absorption rate than the case where only a polyamide compound containing a biopolymer is used. As described above, the present inventors have developed the composite according to the present disclosure with the aim of providing a composite having a higher strength than the composite described in Patent Document 2, and therefore, it was an unexpected effect that the composite also exhibited a very low water absorption rate.
[0086] As shown in the examples described below, the composite according to the present disclosure has a very low water absorption rate, so the polymer contained in the composite is not easily hydrolyzed. Therefore, the composite according to the present disclosure can contribute to preventing cracks in the member to which the composite is applied (such as the exterior material). In this way, the composite according to the present disclosure has the advantage of low water absorption, and is therefore advantageous for a wide range of use in exterior materials and the like.
[0087] As described above, the composite according to the present disclosure has excellent tensile and bending properties, low water absorption, and low environmental impact. Such effects contribute to the achievement of, for example, Goal 11 "Make cities and human settlements inclusive, safe, resilient and sustainable" and Goal 12 "Ensure sustainable consumption and production patterns" of the Sustainable Development Goals (SDGs) proposed by the United Nations.
[0088] [2] Method for producing the composite The method for producing a composite according to the present disclosure includes a step of kneading the glass fiber with a polyamide compound containing dicarboxylic acid units represented by the general formula (1), dicarboxylic acid units represented by the general formula (2), and diamine units represented by the general formula (3) (kneading step).
[0089] The kneading step can be carried out using a known means capable of kneading the polyamide compound and the glass fiber. As the means, for example, known kneaders such as a twin-screw kneading extruder, a kneader kneader, a mixer, etc. can be used. In the method for producing a composite according to the present disclosure, a twin-screw kneading extruder is particularly preferred. The twin-screw kneading extruder is not particularly limited, and a conventionally known device can be used. In addition, the material, shape, rotation direction, gap between each screw, etc. of each screw can be appropriately adjusted by a person skilled in the art.
[0090] The temperature inside the barrel when the polyamide compound and the glass fibers are kneaded is not particularly limited, but is preferably 220°C or higher and 280°C or lower, and more preferably 220°C or higher and 250°C or lower.
[0091] As for other kneading conditions, for example, the screw rotation speed (rpm) is preferably 80 or more and 120 or less, and the torque (N·m) is preferably 50 or more and 70 or less.
[0092] The temperature is lower than that when conventional polyamides having an aliphatic skeleton (such as nylon 6, nylon 12, and nylon 66) are kneaded using a twin-screw kneading extruder. In other words, the composite according to the present disclosure can be prepared at a lower kneading temperature than composites using conventional polyamides because the polyamide compound contains a biopolymer. Therefore, it has the advantage that it can be prepared with low energy and has a small impact on the environment.
[0093] The present disclosure is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present disclosure.
[0094] 〔summary〕 The present disclosure includes the following aspects. <1> A dicarboxylic acid unit represented by the following general formula (1), A dicarboxylic acid unit represented by the following general formula (2), A polyamide compound containing a diamine unit represented by the following general formula (3): Glass fiber and A complex comprising:
[0095] [ka]
[0096] (wherein x is an integer from 6 to 12, y is an integer from 8 to 18, and n is an integer of 1 or more.)
[0097] [ka]
[0098] (z is an integer from 2 to 18.)
[0099] [ka]
[0100] [ka]
[0101] <2> The molar ratio of the dicarboxylic acid unit represented by the general formula (1) to the dicarboxylic acid unit represented by the general formula (2) is 95:5 to 5:95. <1> The complex according to claim 1, <3> <1> or <2> A method for producing the composite according to claim 1, The method for producing a composite includes kneading the polyamide compound and the glass fiber with a twin-screw kneading extruder. EXAMPLES
[0102] The present disclosure will now be described more specifically with reference to examples.
[0103] [1] Preparation of the complex of the present disclosure and measurement of its physical properties (1-1) Synthesis of polyamide compounds The synthesis of the polyamide compound was carried out according to the following scheme. In the following scheme, z=4, m=80, and n=20.
[0104] [ka]
[0105] First, 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BPE) (41.1 g, 100.0 mmol) and THF (300 mL) were placed in a separable flask (1000 mL) under a nitrogen atmosphere. After stirring with a mechanical stirrer for 10 minutes at 0°C, triethylamine (30.8 mL, 220.0 mmol) was added and stirred at 0°C for 10 minutes. Then, acid chloride (1') (57.2 g, 80.0 mmol) and adipol chloride (3.7 g, 20.0 mmol) were dissolved in THF (100 mL) and added dropwise, and the reaction was carried out at 0°C for 4 hours. After the reaction was completed, the product was purified by reprecipitation using water and washed with water and methanol. The product was vacuum dried (80°C, 16 hours). White fibrous, yield: 92.0 g. FT-IR (ATR, cm -1):3290.0(NH,amide),2918.7,2854.1,1653.7(C=O,carbonyl),1601.6,1533.1,1497.5,1461.8,1409.7,1222.6,1174.4,1014.4,831.2,727.0,512.0.
[0106] The polyamide compound was pelletized. The chemical formula of this polyamide compound is shown below. This polyamide compound is also called "PA 80 AC 20 BPE 100 " PA 80 AC 20 BPE 100 is a polyamide compound containing a dicarboxylic acid unit represented by the above-mentioned general formula (1), a dicarboxylic acid unit represented by the general formula (2), and a diamine unit represented by the general formula (3), and corresponds to a conventional biopolymer.
[0107] [ka]
[0108] (1-2) Preparation of Complex The above PA 80 AC 20 BPE 100 The mixture was mixed with glass fiber (GF, Nitto Boseki CSX 3J-451S) in a weight ratio of 70:30 and fed into a small twin-screw extruder HK-25D (L / D=41, Parker Corporation), and extruded to obtain a pellet-like composite. The mixing temperature (temperature inside the barrel) was 230°C. Other mixing conditions were the screw rotation speed (rpm) of 100 and the torque (N·m) of 58.
[0109] When the composite was observed under a scanning electron microscope (SEM), a morphology was observed in which the glass fibers were uniformly dispersed in the polyamide compound.
[0110] (1-3) Differential scanning calorimetry (DSC) measurement The glass transition temperature (Tg) of the composite was determined by subjecting 5 mg of the composite obtained in (1-2) to DSC measurement at a temperature rise rate of 10° C. / min in a temperature range of −50° C. to 280° C. in a nitrogen atmosphere. The DSC measurement was performed using a DSC7000X manufactured by Hitachi High-Tech Science Corporation.
[0111] (1-4) Thermogravimetry and Differential Thermal Analysis (TG / DTA) 5 mg of the composite obtained in (1-2) above was subjected to TG / DTA in a nitrogen atmosphere at a temperature rise rate of 10°C / min and a temperature range of room temperature (20-25°C) to 600°C to determine the thermal decomposition temperature Td (5% weight loss temperature) and the weight loss onset temperature. Thermoplus TG8120 manufactured by Rigaku Corporation was used for TG / DTA.
[0112] (1-5) Measurement of water absorption rate The composite (pellet-shaped) obtained in (1-2) above was subjected to injection molding to form a test piece. The injection molding was performed using a small electric injection molding machine SE18DUZ (manufactured by Sumitomo Heavy Industries, Ltd.) with the composite temperature set to 220°C and the mold temperature set to 28 to 29°C. A JIS K 7161-2 5A type (dumbbell-shaped) test piece was obtained by this injection molding.
[0113] After injection molding, the test pieces in an absolutely dry state were placed in a 200 mL beaker containing 150 mL of pure water without any pretreatment, and immersed. The water temperature was 23°C, and the immersion time was 24 hours. Three test pieces (n=3) were used, and each was immersed under the same conditions. The weights of the test pieces before and after immersion were accurately measured, and the water absorption rate was calculated according to the following formula (1).
[0114] Water absorption rate (%) = (weight of test piece after immersion – weight of test piece before immersion) × 100 / weight of test piece after immersion (1).
[0115] [2] Test methods for mechanical properties (2-1) Tensile test A tensile test was conducted in accordance with JIS K 7161-2:2014 to evaluate the tensile properties, including tensile strength (yield stress), tensile modulus, and tensile breaking strain (elongation at break). The test pieces used in the tensile test were the JIS K 7161-2 5A type (dumbbell-shaped) test pieces described in (1-5) above.
[0116] The width and thickness of the test piece were measured using a universal material testing machine Model 5966 (manufactured by Instron). The measurement conditions were a tensile speed of 10 mm / min, a tensile load of 30 kN, n=5, and a measurement temperature of 23°C.
[0117] (2-2) Bending test A bending test was conducted in accordance with JIS K 7171:2016 to evaluate the bending modulus as the bending property. The composite obtained in (1-2) above was subjected to injection molding under the same conditions as those described in (1-5) above to prepare a rectangular test piece (length 80 mm x width 10 mm x 4 mm) in accordance with JIS K 7171:2016. The rectangular test piece was used for the bending test.
[0118] The width and thickness of the test piece were measured using a universal material testing machine Model 5966 (manufactured by Instron). The measurement conditions were a test speed of 2 mm / min, a maximum load of 2 kN, n=5, and a measurement temperature of 23°C.
[0119] (2-3) Charpy impact test The impact properties were evaluated by performing a notched Charpy impact test in accordance with JIS K 7111-1:2012 to determine the Charpy impact value. The composite obtained in (1-2) above was subjected to injection molding under the same conditions as described in (1-5) above, and a test piece of 80 mm length x 10 mm width x 4 mm (notched) was produced in accordance with JIS K 7111-1:2012. The width and thickness of the test piece were measured during the test. The measurement was performed using a Charpy impact tester (DG-UB, manufactured by Toyo Seiki Seisakusho Co., Ltd.). The measurement conditions were a measurement temperature of 23°C and n=10.
[0120] [3] Evaluation of characteristics The mechanical properties measured by the method described in [2] above are shown in Table 1, and the physical properties measured by the method described in [1] above are shown in Table 2. Fig. 1 is a graph showing the measurement results of the tensile modulus shown in Table 1, and Fig. 2 is a graph showing the measurement results of the flexural modulus shown in Table 1.
[0121] [Table 1]
[0122] [Table 2]
[0123] As shown in Table 1, FIG. 1 and FIG. 2, the composite according to the present disclosure is 80 AC 20 BPE 100 The tensile strength, tensile modulus and flexural modulus are significantly improved compared to those of the composite of the present disclosure. Therefore, it can be said that the composite of the present disclosure has excellent properties such as resistance to breakage, high rigidity and small stress-strain. As described in Patent Document 2, the composite of Patent Document 2 (PA 80 AC 20 BPE 100 A composite of cellulose acetate and talc) measured under the same conditions had a tensile strength of 39.0 MPa, a tensile modulus of 2100.0 MPa, and a flexural modulus of 1520.0 MPa. Therefore, it can be said that the composite according to the present disclosure has tensile properties and flexural properties that greatly exceed those of the composite described in Patent Document 2.
[0124] The tensile strain at break results show that the composites according to the present disclosure have excellent dimensional stability. 80 AC 20 BPE 100 However, as described in Patent Document 2, the value of the composite described in Patent Document 2 (17.0 KJ / m 2 Considering the excellent tensile and flexural properties, the results of the impact properties are within the acceptable range for those skilled in the art.
[0125] As shown in Table 2, the complex according to the present disclosure is 80 AC 20 BPE 100 Since the glass transition temperature and 5% weight loss temperature are higher than those of PA, it can be said that the composite according to the present disclosure has excellent heat resistance. 80 AC 20 BPE 100 The water absorption rate was lower than that of PA. 80 AC 20 BPE 100 is low as shown in Table 2, but the composite according to the present disclosure exhibited an even lower water absorption rate.
[0126] From the above results, it is clear that the composite according to the present disclosure has excellent properties, such as excellent tensile properties, bending properties, and heat resistance, and low water absorption. Therefore, it can be said that the composite according to the present disclosure is a very preferable material for use in the wide range of applications mentioned above. [Industrial Applicability]
[0127] The present disclosure can be used in all components of automobiles, railway vehicles, ships, airplanes, etc.
Claims
1. A dicarboxylic acid unit represented by the following general formula (1), A dicarboxylic acid unit represented by the following general formula (2), A polyamide compound containing a diamine unit represented by the following general formula (3): Glass fiber and A complex comprising: 【Chemistry 1】 (wherein x is an integer from 6 to 12, y is an integer from 8 to 18, and n is an integer of 1 or more.) 【Chemistry 2】 (z is an integer from 2 to 18.) 【Chemistry 3】 【Chemistry 4】
2. 2. The composite according to claim 1, wherein the molar ratio of the dicarboxylic acid unit represented by the general formula (1) to the dicarboxylic acid unit represented by the general formula (2) is from 95:5 to 5:
95.
3. A method for producing the composite according to claim 1 or 2, comprising the steps of: A method for producing a composite, comprising the step of kneading the polyamide compound with the glass fiber.
Citation Information
Patent Citations
Polyamide compound, and method for producing polyamide compound
JP2019137788A
Composite and composite production method
JP2022162256A